Peningkatan Partisipasi Masyarakat Dalam Pembangunan Desa Lokasi Baru Seluma: Kontribusi Mahasiswa KKN Terhadap Pembangunan Desa - Saepudin Saepudin; Dwi Indah Lutfiatin; Reni Kristinawati; Ismail Adi Nugoro; M. Habib Pratama; Veronika Lestari; Ella Astuti; Amelia Anggita; Sopi Amalia; Atika Putriana; Aqilah Luthfiyah Khansa (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Village development is key to the success of national development. Village development has also been supported and established by the government through Law No. 6/2004 on Villages. There are two approaches to village development, namely village development and village development. In village development, community participation has a great influence. The village community is included in the subject of development. The way to increase community participation is to encourage the community to be directly involved in village development planning. Therefore, in this community empowerment activity, researchers take part in participating in village development as a community to encourage other community concerns to actively contribute. In addition, researchers build cooperation between each party involved in development to commit together to achieve common goals. However, in reality, there are factors that can influence community participation, both internal and external. This study will further examine the influence of researcher participation in increasing community participation and what factors influence community participation. The method used in this research is the ZOPP (Ziel, Oriented, Project, and Planning) method. The result of this activity is that the activities that have been carried out have formed a commitment from each party in realizing village development. It should also be noted that community participation is also influenced by two factors, namely internal and external. In this study, the researcher has shown his participation attitude as a community. What the village government must do is to increase community participation by showing good leadership and communication.